2021
DOI: 10.1002/ejoc.202100581
|View full text |Cite
|
Sign up to set email alerts
|

Heteroaliphatic Dimethylphosphine Oxide Building Blocks: Synthesis and Physico‐Chemical Properties

Abstract: Scalable synthesis of saturated heterocyclic dimethyl phosphine oxides (derivatives of azetidine, pyrrolidine, piperidine, and morpholine) is disclosed. The key steps of the synthesis relied on the reactions of HP(O)Me 2 , i. e. the phospha-Mannich (the Kabachnik-Fields-type) condensation with cyclic imines or monoprotected diamines, palladium-catalyzed reactions of alkenyl halides or trifltates (generated from cyclic ketones), as well as base-mediated nucleophilic substitution, Michael addition, or oxirane ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Also, some chemotypes that were not covered in the current review but are certainly relevant to its topic can be found in the literature. As it was mentioned in the Introduction, these include, for example, sulfoximines, [39,527,528] sulfonimidamides [529,530] and their analogs, [531] dialkyl phospine oxides [40,145] -unusual isosteres of amides, sulfonamides, sulfones, and related compounds (Figure 13), as well as deuterated analogues, [41] silicon-containing isosteres, [42] or Ntrifluoromethylated azoles. [43] It is interesting to note that nearly all these examples, as well as most of those discussed in this review, originate from organosulfur, -boron, -phosphorus, -silicon, or -fluorine chemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, some chemotypes that were not covered in the current review but are certainly relevant to its topic can be found in the literature. As it was mentioned in the Introduction, these include, for example, sulfoximines, [39,527,528] sulfonimidamides [529,530] and their analogs, [531] dialkyl phospine oxides [40,145] -unusual isosteres of amides, sulfonamides, sulfones, and related compounds (Figure 13), as well as deuterated analogues, [41] silicon-containing isosteres, [42] or Ntrifluoromethylated azoles. [43] It is interesting to note that nearly all these examples, as well as most of those discussed in this review, originate from organosulfur, -boron, -phosphorus, -silicon, or -fluorine chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…The SuFEx reactions typically use common sulfonylation conditions (Et 3 N, CH 2 Cl 2 ); [130,[136][137][138][139] also, ammonia [140][141][142][143][144][145] or aliphatic amines [146][147][148][149][150][151] can act both as reagents and as bases (Scheme 15A). One more important modification includes reaction of sulfonyl halides and aliphatic N-silylamines in refluxing in MeCN.…”
Section: Applications In Synthetic and Medicinal Chemistrymentioning
confidence: 99%
“…Typically, these reactions are performed with an excess of amine or in the presence of a base like Et 3 N, pyridine, or iPr 2 NEt (Scheme 34); other notable protocols include the use of Ca(NTf 2 ) 2 catalysis [214] and HOBt -1,1,3,3-tetramethyldisiloxane (TMDS) promotion [177] (also requiring the presence of a base). These SuFEx reactions were compatible with the presence of ester, [143,203,[215][216][217][218] nitrile, [40,88,177,219] aromatic [152,220] and aliphatic [177] ketone, chalcone [207] moieties; other groups included azide, [83] phosphine, [177] phosphite, [69] SF 5 , [218] and unprotected carbox- ylic acid. [22,177,221] Furthermore, free alcohol [146,222,223] and phenol [22,177] groups in the starting sulfonyl fluoride, as well as unprotected aniline (in the case of aliphatic amines as Nnucleophiles) [64,177,222,[224][225][226] could be tolerated.…”
Section: Selective Reactions Proceeding At the So 2 F Moietymentioning
confidence: 76%
“…Being a strong electron‐withdrawing group, the SO 2 F fragment is considered as one of the best double bond activators for the nucleophilic conjugate (Michael) addition [60] . Indeed, alkenyl sulfonyl fluorides readily react with a huge variety of C ‐, [60–64] N ‐, [43,62,64–67] S ‐, [25,64,67,68] or P ‐nucleophiles [69] (Scheme 4). For example, Michael addition to the simplest vinyl sulfonyl fluoride was used for the preparation of [ 18 F]‐labelled amino acids [70] and modification of s ‐tetrazine building blocks [71] .…”
Section: Chemoselective Reactions Of Functionalized Sulfonyl Fluoridesmentioning
confidence: 99%
“…For example, vinyldimethylphosphine oxide (1) was introduced into [3 + 2] cycloaddition with azomethine ylide (Scheme 1, C). [6] Diazoalkanes are versatile reagents in organic synthesis that have become increasingly important in recent years due to the development of safe protocols for their in-situ generation. [8][9][10][11][12][13][14] While dialkyl diazophosphonates are widely recognized re-agents in organic synthesis, [15][16][17][18][19][20] diazoalkanes with a phosphine oxide moiety are much rarer (Scheme 1, E), [21][22][23][24] and their reactivity is studied very scarcely.…”
Section: Introductionmentioning
confidence: 99%